Estratégia reprodutiva e gametogênese de Cassidulus mitis Krau, 1954 (Echinodermata: Echinoidea) - Mac Cord, Fábio Sá (2001)
Cassidulus mitis Krau is an endemic species from Rio de Janeiro, Brazil. To verify its reproductive cycle, samples were taken from October 1998 to April 2000 at Vermelha Beach. Sex ratio of 1 (x2= 1.48; a0.05=3.84; DF= l) was found for C. mitis. Reproduction occurs overall the year. Gonadal index (GI) of males was greater than GI of females (x2= 18.33, a0.05=3.84). Reproduction is asynchronous. Males have five gametogenic stages: Early growth, Premature, Mature, Partially spawned and Early growth with partially spawned stage. There is no Spent or Recovery stage as in females. Females have six gametogenic stages: Recovery, Early growth, Premature, Mature, Partially spawned and Spent stage but there is no Early growth with partially spawned stage as in males. Mean diameter of oocytes was 382 μm (DP=49 μm). Mean number of juveniles per female was 99.8 individuals (DP= 108.25; SE= l6.32). Anterior gonads are commonly smaller than posterior ones. Differences in gametogenic stages were found between anterior and posterior gonads. First sexual maturity occurs in individuals larger than 17 mm. Intestine wet weight is about two or three fold higher than test wet weight. It means that C. mitis uses its intestine as a weight belt to avoid displacement.